(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Machine learning (ML) and artificial intelligence (AI) are now pervasive in our lives. There are several cutting-edge gadgets that will make our life easier and more convenient. The technology behind virtual assistants like chat bots is improving in this regard. A chat bot may be able to accurately diagnose a user’s problem based on their replies; while in the past assistants were confined to a small set of frequently asked questions (FAQs). A large and accurate database of medical diseases and their symptoms will be used to train the algorithm. The proposed model uses a decision tree approach to assess the patient’s complexity and provide a result. In response to the user’s inquiries, a desired and highly accurate diagnosis is created. Machine learning (ML) and artificial intelligence (AI) are two technologies that are quickly developing and finding widespread use in modern society.